Penerapan BIM 4D Proyek Rehap Total Gedung Sekolah SMPN 117 Jakarta - Wicaksono, Ari Ikhsan; Purnomo, Adhi; HS, Muh Abdhy Gazali (Institut Teknologi Adhi Tama Surabaya, 2025)
The application of Building Information Modeling (BIM) 4D technology in the total rehabilitation project of SMP Negeri 117 East Jakarta has been proven to contribute significantly to the effectiveness of project management, especially in the aspect of scheduling. By integrating time data into a three-dimensional model, BIM 4D enables a more informative and interactive visualisation of construction progress. This approach not only makes it easier for stakeholders to understand the sequence of implementation, but also helps detect potential scheduling conflicts from the planning stage. Through the Define, Design, Develop, and Disseminate stages used in the Research and Development (RD) approach, the process of developing the 4D BIM model was carried out systematically. Microsoft Project-based scheduling and modelling through the educational version of Autodesk Navisworks successfully produced a visual simulation of the project that illustrates the relationship between construction activities and their implementation time. The results show that BIM 4D can improve cross-disciplinary coordination, reduce the risk of delays due to miscommunication, and optimise resource allocation. In addition, the potential for re-work can be minimised as all stages of construction have been thoroughly simulated prior to implementation in the field. Thus, the implementation of BIM 4D is a strategic solution in supporting efficiency, accuracy, and transparency in the implementation of educational building construction projects.